Impact of Etelcalcetide on Cardiovascular Outcomes and Mortality in Hemodialysis Patients with Secondary Hyperparathyroidism: A Meta-Analysis - Nurul Ramadhani Umareta; Fitri Rahmariani; Zulkhair Ali (Open Access Indonesian Journal of Medical Reviews, 2025)
Secondary hyperparathyroidism (SHPT) is a common complication in hemodialysis patients, contributing to cardiovascular disease and mortality. Etelcalcetide, a novel calcimimetic agent, has shown promise in managing SHPT. This meta-analysis aimed to evaluate the impact of etelcalcetide on cardiovascular outcomes and mortality in hemodialysis patients with SHPT. A systematic search of electronic databases (PubMed, Scopus, Web of Science) was conducted to identify randomized controlled trials (RCTs) comparing etelcalcetide with placebo or other active treatments in hemodialysis patients with SHPT. The primary outcomes were cardiovascular events (composite of myocardial infarction, stroke, heart failure, and cardiovascular death) and all-cause mortality. Pooled risk ratios (RRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Seven RCTs (n=4,520 patients) were included in the meta-analysis. Etelcalcetide was associated with a significant reduction in cardiovascular events (RR 0.85, 95% CI 0.75-0.96, p=0.01) and all-cause mortality (RR 0.88, 95% CI 0.79-0.98, p=0.02) compared to placebo. No significant difference in cardiovascular events or mortality was observed between etelcalcetide and cinacalcet. In conclusion, etelcalcetide appears to be effective in reducing cardiovascular events and mortality in hemodialysis patients with SHPT. Further studies are needed to confirm these findings and to assess the long-term impact of etelcalcetide on cardiovascular health in this population.